HIV-negative status is associated with very early onset of lactation among ghanaian women - Otoo, G.E.; Marquis, G.S.; Sellen, D.W.; Chapman, D.J.; Pérez-Escamilla, R. (Journal of Human Lactation, 2010)
This is a longitudinal cohort study investigating the association between maternal HIV status and the reported onset of lactation. The Research to Improve Infant Nutrition and Growth project recruited 442 mothers from 3 antenatal clinics in the eastern region of Ghana, based on positive, negative, and unknown HIV status. Onset of lactation was assessed by maternal perception and validated with 2 subsamples: measurement of infant breast milk intake (n = 40) and daily infant weight measurement for 2 weeks (n = 150). Multivariate logistic regression was used to identify predictors of very early onset of lactation (onset of lactation < 6 hours). Predictors of very early onset of lactation include HIV-negative status (odds ratio = 2.68; P =.014), multiparity (odds ratio = 2.93; P =.009), vaginal delivery (odds ratio = 2.55; P =.035), and having a male child (odds ratio = 1.86; P =.032). The findings indicate an association between maternal HIV status and very early onset of lactation. © 2010 International Lactation Consultant Association.
Keywords: Exclusive breastfeeding; Ghana; HIV; Onset of lactation